Adenoma‐like adenocarcinoma: a subtype of colorectal carcinoma with good prognosis, deceptive appearance on biopsy and frequent KRAS mutation. Issue 2 (4th June 2015) - Gonzalez, Raul S; Cates, Justin M M; Washington, Mary Kay; Beauchamp, Robert Daniel; Coffey, Robert J; Shi, Chanjuan
Abstract : Aims: A subset of colorectal carcinomas (CRCs) architecturally and cytologically resembles adenomatous change, making them difficult to diagnose on biopsy. This subset has not been well characterized to date. Methods and results: For 35 carcinomas with adenomatous‐like areas (cytological and surface architectural appearance that would be insufficient to warrant a diagnosis of adenocarcinoma if evaluated on biopsy), we recorded staging information, molecular data, clinical outcome, whether precursor adenoma was present and whether previous biopsy had been diagnosed as malignant. Despite advanced T‐category in 23 (66%) tumours, only seven (20%) had nodal metastases, and only five patients (15%) developed distant metastases. Fifteen cases (43%) had been diagnosed as adenoma on biopsy. Twenty‐one resections (60%) showed no residual associated adenoma, including nine called adenoma on biopsy. Median follow‐up was 44 months. Four patients (12%) died of disease; 22 were alive at last follow‐up. KRAS mutation was seen in 14 of 24 (58%) and four of 17 (24%) were microsatellite‐unstable. Patients had significantly improved survival compared to a cohort of patients with conventional well‐differentiated CRC after controlling for age and stage ( P  = 0.011). Conclusions: Adenoma‐like adenocarcinoma is an uncommon variant of CRC with a low rate of metastasis and good prognosis. Biopsy diagnosis of this lesion may be challenging.